Learning Curve Estimation of Indonesian Financial Service Cooperatives: Survey on Indonesian Saving and Loan Cooperatives - Johnny W. Situmorang (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2018)
This study aims to examine the business scale of Indonesian financial service cooperatives (IFSCs) by analyzing their cost functions. By using panel data set of saving and loan cooperatives, this research reveals that the IFSCs industry is running at an increasingly cost to scale condition, yet it is still efficient in the financial services industry market. Micro-scale IFSCs are relatively more efficient than small, medium, and large scale businesses. Furthermore, the result suggests that IFSCs business development strategy should focus on improving internal strength with changes in production technology